The content of Pb and Cd in sediment and oysters in the mangrove area of Kuala Ceurape Bireuen and Udeung Village Pidie Jaya - Azhar, Rossy; Husna, Asmaul; Izwar, Akmal; Nugrahawati, Anis; Putra, Dani Pratama; Kamal, Mustafa (Acta Aquatica: Aquatic Sciences Journal, 2025)
This study aimed to identify the concentration of heavy metals, lead (Pb) and cadmium (Cd), in sediments and oysters (Bivalvia), as well as to examine their relationship with mangrove ecosystem characteristics in Kuala Ceurape (Bireuen) and Udeung Village (Pidie Jaya). Heavy metal concentrations were analyzed using the Indonesian National Standard (SNI) methods, while mangrove species identification was conducted through field vegetation surveys. The results showed that Pb concentrations in sediments ranged from 3.67–15.29 mg/kg with an average of 7.38 mg/kg in Udeung and 8.65 mg/kg in Kuala Ceurape. Cd concentrations in sediments were higher, ranging from 4.69–11.95 mg/kg (average 7.38 mg/kg) in Udeung and 3.54–11.69 mg/kg (average 8.65 mg/kg) in Kuala Ceurape. In oysters, Pb concentrations were recorded at 4.36–9.53 mg/kg in Udeung and 2.16–6.71 mg/kg in Kuala Ceurape, while Cd showed greater accumulation, reaching 17.07–18.13 mg/kg (average 12.71 mg/kg) in Udeung and 1.96–11.21 mg/kg (average 5.16 mg/kg) in Kuala Ceurape. Compared to FAO/WHO and CCME standards, Pb levels in sediments remained below the threshold, but Pb and Cd in oysters and Cd in sediments exceeded safe limits. Vegetation identification indicated the dominance of Rhizophora apiculata, which plays an important role in heavy metal trapping. These findings suggest that mangrove ecosystems function as natural filters of heavy metals, yet bioaccumulation in edible biota such as oysters may pose potential health risks to coastal communities. Keywords: Bioaccumulation; Cd; Mangrove; Oyster; Pb; Sediment